Students’ perception on helpful strategies in resolving reading comprehension test - Hermida, Rita (ACCENTIA: Journal of English Language and Education, 2024)
Reading, similar to other language skills, possesses its own unique techniques and strategies to employ. Every strategy has its distinct purpose and a particular context in which it is applied. Furthermore, it is crucial to employ specific procedures in order to ensure that these techniques are user-friendly. This study specifically focuses on this topic. The objectives of this study are to investigate the reading approaches often employed by students and what strategies they apply in order to increase their reading techniques and abilities. This quantitative study used questionnaire to collect the necessary data, from a sample of 28 second-year students at a private senior high school in Banda Aceh, Aceh. The findings showed that scanning and skimming were the most common reading techniques the students used. In addition, in order to sharpen the reading techniques, most of the students tried to enrich reading material and time management as well. Most of them also joined an extra English class in the afternoon outside the class.  They were enthusiastic to sharpen their ability in critical thinking and background knowledge in reading.  This study hopes to add insights into strategies of reading comprehension for other learners of English.